Social Acceptance of Veil Lecturers in West Sumatra Higher Educational Environments: a Case Study Approach - Benny Benny; Hanif Cahyo Adi Kistoro (STAI Syaichona Moh. Cholil Bangkalan, 2022)
The strength of the negative stigma to women not only makes them ostracized but more of it in some room public women are veiled until they experience rejection, one of them in college high. Different from college another height, in one college high in West Sumatra, women veiled instead of accepted. On this campus, a lecturer has veiled for years. This research generally focuses on social reception. This research explains the acceptance of the lecturer veil at college height and what is just the driving factor a lecturer veiled can be accepted at college tall. Study this use approach study qualitative with research strategy studies case single type explanatory. Use method semi-structured interview with 11 informants from circle leaders, colleagues fellow lecturers, staff education and students. This study found that veiled lecturers at the college were in the accepted category. This means that socially veiled lecturers are not isolated. Though by appearance different from the lecturer in general lecturer veiled not differentiate themself from the environment. Likewise, party campuses do not treat lecturers veiled differently from lecturers others. The reception lecturer veiled this is also encouraged with the method religious lecturer a veil that is not disturbing others as well his personality is intelligent, obedient, disciplined, generous, and considerate.